A new physical insight into the zero-temperature coefficient with self-heating in silicon-on-insulator fin field-effect transistors. (13th January 2021) - Banchhor, Shashank; Chauhan, Nitanshu; Anand, Bulusu
Abstract: The conflicting impacts of temperature on the threshold voltage and mobility, and consequently on the transfer characteristics of a MOSFET, result in a zero-temperature coefficient (ZTC) point. This point is very important for ensuring the stability of the circuit against temperature variations, as the drain current is temperature independent at this bias voltage. In this work, for the first time, we analyze ZTC bias-point instability caused by the self-heating effect (SHE). For this, we discuss the impact of lattice and carrier temperatures, influenced by the SHE, on the ZTC point, which is important in fin field-effect transistors. We report that the SHE causes the ZTC gate bias voltage to be lowered significantly, by about 16% of the overdrive voltage. We also explain the physics of this phenomenon and present a model to explain this change in the ZTC bias caused by the SHE. We discuss the relation between the change in ZTC due to changes in the threshold voltage, saturation velocity, and their temperature derivatives. Our results also show that the drift of the ZTC (i.e. Δ ZTC = ZT C w/oSHE − ZT C withSHE ) is more critical at higher drain-to-source voltages ( V DS ). It is important, from an analog-circuit point of view, to predict the ZTC bias point drift caused by the SHE. Furthermore, a common-source amplifier biased at the ZTC predicted by our model-based method is simulated to validate the stability of the circuit against temperature variations. To improve the device design, the device dimensions are optimized to minimize the drift of the ZTC.